PELATIHAN KADER KESEHATAN MENGENAI PENGELOLAAN KESEHATANLANSIA DI MASA PANDEMI COVID 19 SEBAGAI UPAYA MENINGKATKAN KESEHATAN LANSIA - Nanik Dwi Astutik (Jurnal Pengabdiaan Masyarakat Kasih (JPMK), 2021)
The increasing number of elderly in quantity must get a great attention so that the elderly can pass through their old age successfully, and be able to maintain their health in the midst of the covid 19 pandemic.Tajinan Health Center already has an integrated service program (posyandu) for the elderly that is routinely held every month. However, the activity was temporarily suspended due to constraints on not being allowed to leave the house during Covid 19. Elderly people are among the vulnerable to contracting corona virus because at that age there is a decrease in hormone production and function of the body's organs. Even seniors who already have chronic diseases such as hypertension, diabetes and cancer are more susceptible to contracting due to declining immunity. According to a report issued by the World Health Organization (WHO), the highest death rate due to COVID-19 is the elderly over the age of 80. During the covid 19 period, cadres cannot accompany the elderly directly even though the elderly need to be given knowledge and assistance to be ready to face COVID 19. Elderly people are difficult to digest some of the appeals given by the government related to efforts to keep themselves from being exposed to the COVID-19 virus. The presence of cognitive impairment can make it difficult for the elderly to understand the reasons behind various precautions, such as why they should not leave the house, why they should wear masks, and so on. Therefore, the approach and way of communicating with the elderly needs a little adjustment. Based on the potential of elderly posyandu cadres and the assessment results that have been described, it is necessary to provide knowledge and understanding on elderly health management to improve the understanding of health cadres as an effort to improve the health of the elderly during the covid 19 pandemic.